El hombre del revés : un caso del comisario Adamsberg - Vargas, Fred; Suárez Girard, Anne-Hélène (Madrid : Ediciones Siruela, 2012)
A small mountain community in the French Alps is roused to terror when they awaken each morning to find yet another of their sheep with its throat torn out. One of the villagers thinks it might be a werewolf, and when she's found killed in the same manner, people begin to wonder if she might have been right. Suspicion falls on Massart, a loner living on the edge of town.
Subtitle from cover.
Online resource; title from ePub title page (Digitalia, viewed April 15, 2016)
Keywords: Adamsberg, Jean-Baptiste -- (Fictitious character) -- Fiction; Werewolves -- Fiction; Alps, French (France) -- Fiction; Detective and mystery fiction; Electronic books